Colorectal cytotoxic activities of phenolic constituents isolated from Euphorbia pseudocactus cultivated in Egypt - Mona Ismail, Marwa Hassan Ahmed, Mohamed Zaki, Abeer Moawad, Rabab Mohammed (Journal of Applied Pharmaceutical Science, 2022)
Phytochemical investigation of the ethyl acetate fraction of the Euphorbia pseudocactus aerial parts, family Euphorbiaceae, resulted in the isolation of eight phenolic compounds for the first time from this species. Identification was carried out using different chromatographic and spectroscopic techniques. The isolated compounds were kaempferol (1), ethyl gallate (2), gallic acid (3), astragalin (4), astragalin-6″-gallate (5), nicotiflorin (6), ellagic acid (7), and 1,2,3,4,6-pentagalloylglucose (8). The colorectal cytotoxic activity of the isolated phenolic compounds against the LS-174T and LS-513 (cecum) cell lines was tested using the sulforhodamine B assay. The results revealed that gallic acid possessed colorectal cytotoxic activity with IC50 values of 18.27 and 50.11 μg/ml against the LS-174T and LS-513 cell lines, respectively, while ethyl gallate possessed cytotoxic activity with IC50 value of 25.42 μg/ml against the LS-174T cell line. The results of the other phenolic compounds showed nonsignificant anticancer activity. These findings recommend gallic acid as an anticancer lead compound.
Keywords: Euphorbia pseudocactus, phenolic compounds, colorectal cytotoxic activity, SRB assay